CATUR PURUSA ARTHA LENSA DEKONSTRUKSI DEFINISI PAJAK YANG BERKEADILAN - Darmayasa, I Nyoman; Aneswari, Yuyung Rizka (Jurnal Equity, 2017)
Catur Purusa Artha Lens of Deconstruction Equitable Tax Definition. The study aims to deconstruct the definition of tax with Catur Purusa Artha (CPA) lens. Research using postmodern paradigm focused on modernity disagreement of tax definition based on act. Tax definition for the result of deconstruction namely Dharma in the form of funds contribution that conducted sincerely from individual’s or entity’s Artha to the state which will be distributed based on Kama for the purposes of the state for the welfare of the people. The essence of the deconstruction definition provide a sense of equitable and stimulation of tax compliance.